Operationalizing Multidimensional Constructs in Structural Equation Modeling: Recommendations for IS Research - Wright, Ryan T.; Campbell, Damon E.; Thatcher, Jason Bennett; Roberts, Nicholas (Communications of the Association for Information Systems, 2012)
Although scholars have provided advice regarding how to conceptualize multidimensional constructs, less attention has been directed on how to evaluate structural equation models that include multidimensional constructs. Further, the extant information systems literature has provided little, and sometimes contradictory, direction on how to operationalize multidimensional constructs. This gap in how we approach multidimensional constructs merits attention because: (1) establishing construct validity is critical to testing theory and (2) recent advances in software enable testing models with multidimensional constructs more readily. Therefore, this tutorial (1) describes different forms of multidimensional constructs and (2) illustrates how to integrate superordinate and aggregate multidimensional constructs in structural equation models. In doing so, we offer guidelines and examples for how to conduct and evaluate research using multidimensional constructs.